1994
DOI: 10.1093/jmedent/31.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Cold Acclimation, Diapause, and Geographic Origin Affect Cold Hardiness in Eggs of Aedes albopictus (Diptera: Culicidae)

Abstract: Eggs of five strains of Aedes albopictus (Skuse) were obtained in both diapause and nondiapause conditions and exposed to various cold acclimation regimes in the laboratory, after which they were subjected to diverse chilling treatments. Larvae that survived chilling as eggs survived to the pupal stage. Eggs of Aedes aegypti (L.) and Aedes triseriatus (Say) were included as control species. Eggs of temperate Ae. albopictus were more cold-hardy than eggs of Ae. aegypti but less cold-hardy than the eggs of Ae. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
111
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 0 publications
3
111
0
2
Order By: Relevance
“…In another study of diapause under field conditions, Hanson and Craig (1994) found that diapause eggs of a temperate strain of Ae. albopictus exhibited relatively high overwinter survivorship of 78% at a South Bend Indiana field site in 1990-1991, but no eggs survived the winter of [1989][1990].…”
Section: Diapause Ecology Of Ae Albopictusmentioning
confidence: 98%
See 3 more Smart Citations
“…In another study of diapause under field conditions, Hanson and Craig (1994) found that diapause eggs of a temperate strain of Ae. albopictus exhibited relatively high overwinter survivorship of 78% at a South Bend Indiana field site in 1990-1991, but no eggs survived the winter of [1989][1990].…”
Section: Diapause Ecology Of Ae Albopictusmentioning
confidence: 98%
“…albopictus in the mid-western United States, Hawley et al (1989) demonstrated that diapause eggs exhibited increased overwinter survivorship relative to nondiapause eggs at three field sites-South Bend, IN; Indianapolis, IN; and Evansville, IL. This increased overwinter survivorship of diapause eggs during the midwestern winter is presumably due to the increased cold tolerance of diapause eggs (Hanson and Craig 1994), as well as enhanced desiccation resistance (Sota andMogi 1992, Urbanski et al 2010) and increased lipid content (Reynolds et al 2012). Interestingly, Hanson and Craig (1995b) showed that although cold acclimation and diapause independently decreased the lower lethal temperature of eggs from À8 C to À12 C, these temperatures are still substantially above the supercooling point of $À27 C, which was not affected by either diapause or cold acclimation (Hanson and Craig 1995b).…”
Section: Diapause Ecology Of Ae Albopictusmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the natural distribution area of A. albopictus includes both tropical and quite temperate areas (Hawley, 1988). Second, laboratory research, modelling and fi eld observations have further confi rmed the great ability of A. albopictus to also adapt to colder temperate climates (Hanson and Craig, 1994;Kobayaski et al, 2002;Delatte et al, 2009;Lacour et al, 2014). Th ird, modelling based on data collected in the south of France shows that, at the regional scale, human transportation is the most important factor in the dispersion of A. albopictus and that land use is a major factor in its establishment (Roche et al, 2015).…”
Section: Methodology: Diachronic Observation and Complementarity Betwmentioning
confidence: 99%